Woman through the Lens of the Polish - and Russian-Language Magazines „Dobre rady” – «Добрые советы» - Górska, Marzena (Respectus Philologicus, 2013)
This article attempts to characterize the Polishlanguage magazine Dobre rady in comparison with its Russian-language version Добрые cоветы. This article applies a comprehensively targeted discursive comparison of content to analyze thematic, semantic, cultural, social, structural, and linguistic data. The magazines are related to each other and form a whole, and both affect the perception of a specific group of readers. The analyzed magazines are monthlies of a handbook character, which help readers to take care of children, their health and beauty, and the home. They also provide information on how to resolve legal and financial issues, publish recipes, and entertain their readers. The analysis reveals that in these magazines, a personal pattern emerges of a woman whose main task is to combine the roles of worker, wife, mother, and housekeeper. The presented model comprises two types of women—the stereotypical, empathetic woman whose most important values are marriage and the home, and the rebel woman—a professional, for whom the realization of her own ambitions and the cult of the body are in the first place. The article reflects both theoretical and practical interests, and may be useful not only to those who read the magazines (modern women, housewives burdened with family problems, etc.) but also more broadly—taking into account women who do not fit the outlined image. The comparative nature of the article allows reflection on psychological as well as general cultural issues.